Ten trends in international mediation - ALEXANDER, Nadja (Institutional Knowledge at Singapore Management University, 2019)
In this essay, the author offers an international overview ofmediation developments in the 21st century and identifiescontemporary influences such as artificial intelligence andthird-party funding. With a focus on mediation ofcross-border disputes, the author identifies ten trends ininternational mediation. These include the changing profileof cross-border disputants and corresponding developmentsin international mediation practice and law. The role ofmediators and lawyers is analysed in the context of theprofessionalisation of the field through credentiallinginitiatives and the new specialisation of mediation advocacy.With the growing internationalisation of mediation, there hasbeen greater appreciation of diverse practice models and thecultural assumptions underpinning them. These developmentsare explored along with the increasing and differentiated useof mediation in mixed mode procedures and a considerationof how technology is challenging conventional understandingsof face-to-face mediation. Finally, two topics not traditionallyassociated with mediation, namely apology legislation andthird-party funding, are examined with a view to how theymay influence the future of mediation.